Tinjauan Yuridis Tentang Pertanggungjawaban pada Kantor Perusahaan Daerah Air Minum (PDAM) dalam Menangani Kebocoran Pipa Air (Studi Kasus di PDAM Blora) - Anggraini, Sofia, Inayah, S.H., M.H (2017)
Accountability is intended to fix all conditions due to the failure of the activities of the company. This study aims to determine the relationship between the central service office service office areas related to leakage of water pipe PDAM Blora, to determine obstacles in the implementation of accountability associated with pipeline leaks water taps, and to determine the leakage prevention efforts in addressing water pipe taps. The research method used juridical empirical method with type research inventory of positive law and legal research to find In-Concreto as to determine the suitability of concrete events studied with the existing norms. The results showed that the company's problems that often happens is the water pipe leakage both technical and non-technical. To make the process of accountability can be done by holding a working agreement between the company and labor outsourcing to achieve a goal. Keywords: Accountability, PDAM Blora, Water leak.